A novel strategy for assembling youth national teams - Naboychenko E.S. ,; Istomin S.O. ,; Ezhov A.N. ,; Kondratovich S.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to create a groundbreaking method for selecting national youth teams. Methods and structure of the study. A group of 52 young athletes, aged 16, from hockey schools in the Ural Federal District, took part in the assessment. They had been playing hockey for 11 to 12 years. The assessment was conducted between July 2024 and December 2025. Results and conclusions. The advanced methodology for assembling youth hockey teams emphasizes the importance of considering the fundamental aspects of a player's abilities and their psychological and physical condition. The novel approach to team building incorporates a systematic process that combines modern techniques for sports selection and monitoring the psychological and physical state of athletes, utilizing observation and gradual evaluation of their performance in competitive events. This approach also considers the necessary and sufficient indicators of an athlete's psychological and physical condition, as well as their individual and potential capabilities. By analyzing the promising attributes of an athlete, we can determine whether they meet the selection criteria for the national team.